The Influence Of Religiosity And Reference Groups On Decision To Purchase Halal Labeled Products - Amilia, Suri; Fuad, Muhammad; Zati, Muhammad Rizqi; Faridy, Najihatul; Gunanjar, Imam (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to analyze the influence of religiosity and reference groups on purchasing decisions for halal-labeled products. This study uses multiple linear regression analysis. Based on the results of the t-test, religiosity and reference groups partially have a significant influence on purchasing decisions for halal-labeled products. Meanwhile, the F-test shows that religiosity and reference groups simultaneously influence purchasing decisions for halal-labeled products. Through the analysis of the coefficient of determination, it can be explained that religiosity and reference groups have an influence on purchasing decisions for halal-labeled products by 46.6%, the difference of 53.4% is influenced by variables outside this study.